Data from: Incorporating herders' knowledge and ecosystem-based adaptation strategies in local decision-making - Hausner, Vera Helene; Engen, Sigrid (Zenodo, 2019)
1. Ecosystem-based adaptation (EbA) relies upon the capacity of ecosystems to buffer communities against the adverse impacts of climate change. Maintaining ecosystems that deliver critical services to communities can also provide co-benefits beyond adaptation, such as climate mitigation and protection of biological diversity and livelihoods. EbA has to a limited extent drawn upon indigenous-and local knowledge (ILK) for defining critical services and for implementing EbA in decision-making. This is a paradox given that the primary focus of EbA is to enable communities to adapt to climate change. 2. The purpose of this study was to elucidate EbA strategies that take into account the knowledge of Sámi reindeer herders about pastures in tundra regions. We first examined what constitutes critical services as perceived by Sámi reindeer herders through a synthesis of data and literature. We thereafter used content analysis of 91 land use cases from 2010-2018 to investigate to what extent the herders' knowledge and maps over seasonal pastures and migratory routes are used in local decision-making. Finally, we propose EbA strategies of relevance to Sámi communities and pastoral communities elsewhere. 3. Our analysis revealed that reindeer herders and organizations representing their interests perceived threats from green energy development, tourism, recreation, public road construction and powerlines. These threats included the loss of key habitats and the loss of connectivity for migration between seasonal pastures. Herders' knowledge is incorporated through participatory tools to protect the ecosystems and services crucial for herders, but multiple competing land uses result in incremental loss of pastures regardless. 4. Synthesis and application. Pastoralists need access to diverse resources on seasonal pastures and the ability to move between pastures when snow, ice, rainfall and the timing of critical service supplies changes. Drawing on herders' knowledge to elicit EbA strategies is vital for buffering the adverse ...